Removal of Color Scratches from Old Motion Picture Films Exploiting Human Perception. (28th September 2008) - Bruni Bruni, Vittoria Vittoria; Ferrara Ferrara, Paola Paola; Vitulano Vitulano, Domenico Domenico
Abstract : In this paper a unified model for both detection and restoration of line scratches on color movies is presented. It exploits a generalization of the light diffraction effect for modeling the shape of scratches, while perception laws are used for their automatic detection and removal. The detection algorithm has a high precision in terms of number of detected true scratches and reduced number of false alarms. The quality of the restored images is satisfying from a subjective (visual) point of view if compared with the state-of-the-art approaches. The use of very simple operations in both detection and restoration phases makes the implemented algorithms appealing for their low computing time.